La merce-dono. Etnografia della Vendita: promozioni, omaggi, fiducia - Mantoani, Gianluca (EtnoAntropologia, 2014)
The retail surface is the result of an institutional frame who rules the way by which people interacts with commodities. It is therefore a source of information about social dynamics, an anthropological source, who must be understood on the field. This paper shows that linking goods to free gifts, a well-known sales strategy, works through the basic relational value of “trust”, usually considered far from the typical habitus of trade relations but instead fundamental to let selling good express theyr own “commodity candidacy”.